Becoming Familiar With a Newly Encountered Face: Evidence of an Own-Race Advantage. (August 2018) - Zhou, Xiaomei; Matthews, Claire M.; Baker, Kristen A.; Mondloch, Catherine J.
Adults' ability to match identity in images of unfamiliar faces is impaired for other- compared with own-race faces; their ability to match identity in images of familiar faces is independent of face race. Exposure to within-person variability in appearance plays a key role in face learning. Past research suggests that children need exposure to higher levels of variability than adults to learn a new face—a difference that has been attributed to experience. We predicted that adults' limited experience with other-race faces would result in their needing exposure to higher levels of variability when learning other- compared with own-race faces. We introduced adults to four new identities (two own-race; two other-race) in one of the three conditions: a single image, a low-variability video (filmed on 1 day), or a high-variability video (filmed across 3 days). Adults' ability to recognize new instances of learned identities improved in the low-variability condition for own-race faces but only in the high-variability condition for other-race faces. We discuss learning mechanisms that might drive this difference—a difference we attribute to experience.